Temperature and relative humidity changes during mass production of Ephestia kuehniella (Lepidoptera, Pyralidae). - Tavares, João (2013)
Resumo da comunicação apresentada no VI Congreso Ibérico de Entomología, XIII Jornadas de la AeE & VII Congreso de la Spen. Madrid, 26 -30 de Septiembre de 1994.